Si Miskin selalu ada padamu Suatu Kajian Stigmatisasi terhadap Pak Ogah ditinjau dari Yohanes 12:8 - Pabian L Masola (STT KINGDOM BALI, 2022)
This research was motivated by the emergence of various hunger cries from the public to the government because of the paralysis of the economy caused by the C19 pandemic. This phenomenon occurs all over the world without exception of rich or poor countries. But do all feel hunger, Who is most affected by this situation? The answer must be the poor poor. This research is used to answer two main problems, namely how do people in a community categorize and stigmatize Pak Ogah (a person who stands on the road to regulate road traffic, so as not to jam) during the post-pandemic 19 famine response? can they accommodate their children's education and daily life at the end of the c19 pandemic? The results of this study indicate that the community in the Pak Ogah community has four processes in stigmatizing the Pak Ogahs. The four processes are understanding the Pak Ogah phenomenon, categorizing Pak Ogah, stigmatizing Pak Ogahs, and providing responses and attitudes in respond to Mr. Ogah who is around their environment.